Compatibility of visibility and harmony of pictogram: focus on restroom mark / Iwasaki Yuta ... [et al.] - Yuta, Iwasaki; Yuji, Matsumoto; I-kang Li, Andrew; Ryusuke, Naka (2018)
In recent years, there are many various design signs to guide people. In the signature "pictogram" which enables guidance without using words is often used. However, when looking into a building, a signature using the pictogram is given its own design to match with the indoor space, and signs which are difficult for the user to understand are distributed. It can be thought that these pictograms are being redesigned to adapt to architecture. Therefore, this study aimed for a sign plan which is easy for users to understand, and the neccessity in having one standard pictograms harmonizing with various buildings. Visibility is important for pictograms, and in this research, the objective is to study the conditions of pictograms that are compatible in visibility and harmony. For reference to the research conducted for each generation, an experiment using the pictogram of the Japanese Industrial Standard toilet mark, which had high recognition of all generations was conducted. The pictograms were divided based on gender that is pictograms for men and for women. The existing designs filled with colour and new designs with only contour lines are more harmonious using textures of concrete, brick, white wall, wood pictograms were synthesized. The researchers analysed and compared with all of these textures with the pictograms . As a result, the design of the outline of the pictogram for men and the pictogram for women is more harmonious in all scenes. The findings displayed that both male pictograms and female pictograms showed significant differences in the two scenes, and a significant trend was observed in the remaining two scenes. Experiments on the width of the contour line using 4 scenes images were conducted. The same experiment was conducted as comparison on the pictograms of the line widths with the greatest thickness. As a result, there was not much difference in the width of the width of the contour line of the pictogram in all scenes of male pictograms and female pictograms. The study also will highlight the effect on visibility and harmony by shape and color as future prospect.